Beyond neoliberal tourism: A critical review - Kosmas, Petros C.; Vatikioti, Aggeliki (My University, 2024)
Several countries, particularly those adversely affected by the recent economic crisis of 2007-2008, rely heavily on tourism for economic growth. However, excessive tourism growth within a neoliberal economy can have negative effects both on natural and cultural resources as well as on society. Recently, a growing movement of academics and activists seems to be urging a redefinition of tourism as the result of neoliberal tourism. Particularly at a time when the spread of COVID-19 had targeted an industry that was experiencing unprecedented growth. Taking the premise that neoliberal tourism is a major contributor to environmental and social unsustainable development, this critical review describes the externalities of excessive tourism growth. Furthermore, this chapter intends to contribute to the discussion of sustainable tourism by exploring new opportunities aligned with degrowth and post-capitalist perspectives that prioritize community involvement, environmental sustainability and social justice.
Keywords: Neoliberal tourism; Tourism externalities; Degrowth; Decroissance; Detourism; Post-capitalist tourism; Sustainable tourism; Overtourism; Touristification; Touristphobia; Trexit